Recombination between a temperature-sensitive mutant and a deletion mutant of Rous sarcoma virus. - Kawai, S (1976)
Cells doubly infected with two mutants of the Schmidt-Ruppin strain of Rous sarcoma virus (RSV), ts68, which is temperature sensitive for cell transformation (srcts), and a deletion mutant, N8, which is deficient in the envelope glycoprotein (env-), produced a recombinant which carried the defects of both parents. The frequency of formation of such a recombinant was exceptionally high and made up 45 to 55% of the progeny carrying the srcts marker. By contrast, the reciprocal recombinant, which is wild type in transformation (srcts) and contains the subgroup A envelope glycoprotein (envA), was almost undetectable. This remarkable difference in the frequency of the formation of the two possible recombinants suggests that a unique mechanism may be involved in the genetic interaction of the two virus genomes, one of which has a large deletion. When an RNA-dependent DNA polymerase-negative variant of the N8 (N8alpha) was crinants also became deficient in the polymerase. Cells infected by the srctsenv- recombinant were morphologically normal at the nonpermissive temperature (41 degrees C) and susceptible to all subgroups of RSV. The rate by which the wild-type RSV transformed the recombinant-preinfected cells was indistinguishable from that of transformation of uninfected chicken cells by the same wild-type virus. This indicates that no detectable interference exists at postpenetration stages between the preinfected and superinfecting virus genomes and confirms that the expression of the transformed state is dominant over the suppressed state.